The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1053/j.semnuclmed.2012.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Use of Dual-Point Fluorodeoxyglucose Imaging to Enhance Sensitivity and Specificity

Abstract: Positron emission tomography (PET) and positron emission tomography/computed tomography imaging with fluorodeoxyglucose (FDG) are widely used as a powerful evaluation modality in oncological nuclear medicine not only for detecting tumors but also for staging and for therapy monitoring. Nevertheless, there are numerous causes of FDG uptake in benign processes seen on PET images. In fact, the degree of FDG uptake is related to the cellular metabolic rate and the number of glucose transporters. FDG accumulation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 67 publications
2
42
0
Order By: Relevance
“…[2][3][4][5] In addition, the same trend has also been reported in malignant breast lesions. The increasing uptake of FDG over time in breast malignancies has been suggested to be helpful in enhancing the diagnostic accuracy of FDG-PET studies.…”
Section: O R I G I N a L R E S E A R C Hsupporting
confidence: 52%
See 1 more Smart Citation
“…[2][3][4][5] In addition, the same trend has also been reported in malignant breast lesions. The increasing uptake of FDG over time in breast malignancies has been suggested to be helpful in enhancing the diagnostic accuracy of FDG-PET studies.…”
Section: O R I G I N a L R E S E A R C Hsupporting
confidence: 52%
“…6 Several studies have reported that dual time point FDG-PET examinations with relative changes in uptake improve the sensitivity and accuracy of diagnosing breast cancer. 2,3,[6][7][8][9][10][11] The standardized uptake value (SUV) is widely used for quantitative evaluation in FDG-PET studies. However, the SUV varies depending on the PET image quality, submit your manuscript | www.dovepress.com…”
Section: O R I G I N a L R E S E A R C Hmentioning
confidence: 99%
“…The perilesional location of 18 F-FDG uptake, as well as negative findings at the early acquisition time despite the presence of viable parasite, suggests that the periparasitic immune infiltrate is responsible for the increased uptake of 18 F-FDG in AE. Unlike most of the usual inflammatory or infectious diseases that have been studied using 18 F-FDG PET (30,31), AE lesions do not include any polymorphonuclear neutrophils, thus perhaps explaining why delayed acquisition reinforced the PET images rather than decreasing the signal on dual-time-point imaging. A rather unusual metabolism of the periparasitic immune cells that are maintained in a chronic status of tolerance might also explain an increase in 18 F-FDG uptake with time (32).…”
Section: Discussionmentioning
confidence: 99%
“…Interpretation and comparison of SUV values is difficult, depending on technical, biological and physical parameters (20). Although an SUV max of 5 is frequently proposed as a threshold (14,21) can be made from data of other centers because of different technical parameters (22,23). The four patients with uninterpretable results in our patient set had a low initial SUV max (<5).…”
Section: Discussionmentioning
confidence: 83%